Rapid prototyping with Framer : quickly and easily create interactive prototypes - Chen, Kenny; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"In this Rapid Prototyping with Framer training course, expert author Kenny Chen will teach you how to create your own interactive prototypes with Framer. This course is designed for the absolute beginner, meaning no experience with Framer is required. You will start by learning how to download Framer Studio and navigate the interface. From there, Kenny will teach you about CoffeeScript for Framer. This video tutorial also covers layers, including how to position and size layers, as well as how to import designs from Sketch and Photoshop. You will also learn about animation and how to work smarter and faster using layer and animation defaults. Kenny will then teach you about events, states, and components. Finally, you will learn how to create and use modules. Once you have completed this computer based training course, you will be fully capable of creating your own interactive prototypes using Framer."--Resource description page.
Title taken from title screen (viewed August 4, 2015).
Publisher and date of publication taken from resource description page.
Presenter, Kenny Chen.
Keywords: Interactive multimedia -- Design; Rapid prototyping; Electronic books